Pemanfaatan TIK sebagai Infrastruktur Pendidikan: Tantangan dan Peluang di Era Digital - Umul Nazira; Ulfah Zahra; Gusmaneli (Journal Of Informatics And Busisnes, 2024)
The role of Information and Communication Technology (ICT) in Indonesian education is crucial for expanding learning access and improving educational quality. ICT enables the use of e-learning platforms, interactive educational apps, and data-driven learning tools that can be tailored to students' needs. However, the utilization of ICT faces challenges, including limited internet access in remote areas, disparities in technological infrastructure, and low digital literacy among educators and students. Therefore, strategies for optimizing ICT, such as enhancing teacher training, providing equitable digital infrastructure, and developing local content based on the curriculum, are essential. With proper utilization, ICT has the potential to enhance learning effectiveness, enrich 21st-century competencies, expand global collaboration, and bridge educational gaps between regions.The role of Information and Communication Technology (ICT) in Indonesian education is crucial for expanding learning access and improving educational quality. ICT enables the use of e-learning platforms, interactive educational apps, and data-driven learning tools that can be tailored to students' needs. However, the utilization of ICT faces challenges, including limited internet access in remote areas, disparities in technological infrastructure, and low digital literacy among educators and students. Therefore, strategies for optimizing ICT, such as enhancing teacher training, providing equitable digital infrastructure, and developing local content based on the curriculum, are essential. With proper utilization, ICT has the potential to enhance learning effectiveness, enrich 21st-century competencies, expand global collaboration, and bridge educational gaps between regions.